2017
DOI: 10.1007/s10071-017-1096-4
|View full text |Cite
|
Sign up to set email alerts
|

Great ape gestures: intentional communication with a rich set of innate signals

Abstract: Great apes give gestures deliberately and voluntarily, in order to influence particular target audiences, whose direction of attention they take into account when choosing which type of gesture to use. These facts make the study of ape gesture directly relevant to understanding the evolutionary precursors of human language; here we present an assessment of ape gesture from that perspective, focusing on the work of the “St Andrews Group” of researchers. Intended meanings of ape gestures are relatively few and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
157
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(168 citation statements)
references
References 67 publications
(134 reference statements)
2
157
0
Order By: Relevance
“…Arnold & Zuberbühler, ), as opposed to the redundancy present in the ape gestural repertoire (e.g. Byrne et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Arnold & Zuberbühler, ), as opposed to the redundancy present in the ape gestural repertoire (e.g. Byrne et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, studies on wild communities provided evidence that the available repertoires are largely innate and species‐typical (Genty et al, ; Hobaiter & Byrne, ; Graham, Furuichi & Byrne, ). After a lively debate on the mechanisms of gesture acquisition, several researchers concluded that the forms of gesture types (the ‘tool‐set’ or available repertoires) are largely genetically anchored (Byrne et al, ), whereas their usage in relation to their context and social environment (the ‘tool application’) is affected by interactional experiences throughout life (Bard et al, ; Fröhlich & Hobaiter, ; Liebal, Schneider & Errson‐Lembeck, ; Pika & Fröhlich, ). Early gestural communication in chimpanzees, for instance, is influenced by the number of interaction partners and interaction rates with non‐maternal conspecifics (Fröhlich et al, ).…”
Section: Cognitive Mechanisms Identified In Non‐human Gestures and Vomentioning
confidence: 99%
See 1 more Smart Citation
“…This is in contrast to findings in great apes where repertoire size is negatively related to age (Genty et al 2009; Hobaiter and Byrne 2011). There it is proposed apes gradually learn which gestures from a portfolio work best and so omit superfluous ones with experience (Byrne et al 2017). With the so-called ‘redundancy’ taking place adult apes consequently demonstrate fewer gestures.…”
Section: Discussionmentioning
confidence: 99%
“…Attempts to teach great apes to talk have largely failed, but greater success has been achieved using simplified forms of sign language (Patterson and Gordon, 2001) or keyboards containing arrays of word-like symbols (Savage-Rumbaugh et al, 1998). Byrne et al (2017) list 84 different communicative gestures arising from the studies of great apes' gestures, and note that they are goal directed and intentional, unlike most primate calls. To be sure, there is little evidence for sentence-like structure, but chimpanzee gestures suggest a natural platform for more complex sequences.…”
Section: The Production Problemsmentioning
confidence: 99%